The unpolarized macronova associated with the gravitational wave event GW 170817. (November 2017) - Covino, S.; Wiersema, K.; Fan, Y.; Toma, K.; Higgins, A.; Melandri, A.; D'Avanzo, P.; Mundell, C.; Palazzi, E.; Tanvir, N.; Bernardini, M.; Branchesi, M.; et al.
Abstract The merger of two dense stellar remnants including at least one neutron star is predicted to produce gravitational waves (GWs) and short-duration gamma ray bursts1, 2 . In the process, neutron-rich material is ejected from the system and heavy elements are synthesized by r-process nucleosynthesis1, 3 . The radioactive decay of these heavy elements produces additional transient radiation termed kilonova or macronova4–10 . We report the detection of linear optical polarization, P  = (0.50 ± 0.07)%, 1.46 days after detection of the GWs from GW 170817—a double neutron star merger associated with an optical macronova counterpart and a short gamma ray burst11–14 . The optical emission from a macronova is expected to be characterized by a blue, rapidly decaying component and a red, more slowly evolving component due to material rich in heavy elements—the lanthanides15 . The polarization measurement was made when the macronova was still in its blue phase, during which there was an important contribution from a lanthanide-free outflow. The low degree of polarization is consistent with intrinsically unpolarized emission scattered by galactic dust, suggesting a symmetric geometry of the emitting region and low inclination of the merger system. Stringent upper limits to the polarization degree from 2.45–9.48 days post-burst are consistent with the lanthanides-rich macronova interpretation. A double neutron star merger gave rise to the gravitational-wave event GW 170817, with counterpart electromagnetic radiation in the optical and gamma-ray spectra. Polarization measurements of the optical emission reveal a lanthanide-rich macronova.